Postpartum lifestyle modifications for women with gestational diabetes: A qualitative study. (September 2020) - Krompa, Katerina; Sebbah, Simon; Baudry, Camille; Cosson, Emmanuel; Bihan, Hélène
Abstract: The prevalence of gestational diabetes mellitus increased to 8% in France in 2012, and the risk of developing type 2 diabetes after receiving a gestational diabetes diagnosis increases 7-fold. Education delivered during pregnancy aims to reduce this risk by reminding women to maintain dietary and lifestyle modifications after delivery. Objective: The primary objective of this study was to describe and analyze the feelings and daily lifestyle changes, including physical activity and dietary changes, among women who experienced gestational diabetes and the roles played by their general practitioners during follow-up. Study design: We conducted a qualitative study examining women's attitudes during the 6–12 months postpartum, after receiving a gestational diabetes diagnosis and associated education. All women participated in semi-structured, individual, telephone-based interviews. Results: Out of 47 patients contacted, we interviewed 16 women. All interviewed women modified their behaviors, at least slightly, and described changes that included more balanced diets and the incorporation of mild physical activity. Lack of time, lack of awareness regarding the long-term risk of developing type 2 diabetes, resistance to long-term dietary changes, and cultural habits were identified as the primary barriers to long-term lifestyle modifications, whereas family support was found to be beneficial. The reported interactions between each woman and her physician appeared to be weak. Conclusion: Our study showed that educational attitudes and preventive interventions must be reinforced, especially during the long-term, and not only during the immediate postpartum period. Raising awareness among primary care physicians regarding the need to provide continuous education for this high-risk population appears to be necessary.